Understanding the perceived importance of disclosing ethical concerns underlying data visualizations - Junger, Ana Caroline Ferreira; Barbosa, Simone Diniz Junqueira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2025: Anais do XXIV Simpósio Brasileiro sobre Fatores Humanos em Sistemas ComputacionaisDO - 10.5753/ihc.2025.10920, 2025)
Introduction: Data visualizations are increasingly being used as a means of conveying data. However, ethical issues of data visualizations are still an understudied topic. Objective: Our objective is to understand how ethical aspects relate to data visualization and how visualization readers perceived the importance of disclosing ethical concerns underlying data visualizations. Methodology: We reviewed the literature to understand how ethical aspects relate to data visualization and then evaluated, with visualization readers, what aspects they deem more important in two different scenarios. Results: The results show that the order of priority varies between scenarios and between participants’ profiles, but understanding the target audience’s needs, the visualization objective, and how the data was collected features among the most important aspects in every case. The items perceived as most important were not aligned with those found more frequently in the literature, which highlights the importance of evaluating what has been found in the literature with real participants.